A high-toughness powder metallurgy titanium alloy and a preparation method thereof
Patent Information
- Application Number
- CN202611351842.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-09
AI Technical Summary
目前最高钢级油井管V150的冲击韧性可达100 J/cm²以上,而传统中、高强度钛合金在室温下的冲击韧性普遍不足,难以满足复杂冲击工况下的使用需求
[0017]总体而言,通过本发明所构思的以上技术方案与现有技术相比,本发明提供的高强韧粉末冶金钛合金及其制备方法:
Smart Images

Figure CN122879552A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of titanium alloy materials and powder metallurgy, and more specifically, relates to a high-strength and high-toughness powder metallurgy titanium alloy and its preparation method. Background Technology
[0002] Titanium alloys are widely used in aerospace, marine engineering, biomedical, and oil and gas exploration equipment due to their high specific strength, excellent corrosion resistance, good biocompatibility, and wide operating temperature range. As oil and gas resource extraction continues to expand into deeper, higher-pressure, higher-temperature, and more impact-sensitive environments, the service environment places higher demands on the comprehensive performance of structural materials, especially the synergistic improvement of high strength and high impact toughness.
[0003] During deep and ultra-deep well drilling and production, critical load-bearing components such as drill strings and casing are subjected to long-term cyclic impact loads, wellbore collisions, centroidal vortex effects, and the combined effects of various stresses including tension, compression, torsion, and high internal pressure. Their impact resistance directly affects the fracture risk of components and the overall operational safety. Impact toughness, as an important indicator of a material's ability to resist transient loads and crack propagation, is one of the key performance characteristics for ensuring the long-term stable service of downhole structural components. Currently, the highest grade of oil well tubing, V150, can achieve an impact toughness of over 100 J / cm², while traditional medium- and high-strength titanium alloys generally lack sufficient impact toughness at room temperature, making it difficult to meet the requirements of use under complex impact conditions.
[0004] Patent CN110229976B discloses a high-strength and high-toughness titanium alloy containing Nb and Ni. Through solution-aging treatment, it can achieve a yield strength ≥900 MPa, but its impact toughness is only 44~56 J / cm², making it difficult to withstand the strong impact loads under deep well conditions. Furthermore, the presence of Ni in this alloy makes it prone to segregation during smelting, hindering the acquisition of stable mechanical properties. Patent CN120026211A discloses an 827 MPa-grade titanium alloy for deep well drill pipes and its preparation method. It achieves a balance between strength and toughness through Nb and Ru microalloying and a high-strain extrusion-sub-temperature annealing process. Although its toughness is superior to conventional α+β titanium alloys, it is still far below the urgent need for high impact toughness materials in deep well drill strings, short-radius wells, and ultra-deep wells.
[0005] In conclusion, the development and preparation of high-strength and high-toughness titanium alloy materials remains one of the major challenges in the increasingly demanding oil and gas drilling and production field. There is an urgent need to develop a titanium alloy material that combines high strength and high toughness to improve the service safety and overall service life of key components in complex downhole conditions. Summary of the Invention
[0006] In view of the above-mentioned defects or improvement needs of the existing technology, the present invention provides a high-strength and high-toughness powder metallurgy titanium alloy and its preparation method, which effectively overcomes the problem that traditional titanium alloys cannot achieve both strength and toughness. The powder metallurgy titanium alloy provided by the present invention has high strength, good plasticity and impact toughness, and has broad application prospects in extreme service conditions such as oil drilling.
[0007] To achieve the above objectives, according to one aspect of the present invention, a high-strength and high-toughness powder metallurgy titanium alloy is provided, which is composed of the following components by mass percentage: 2-4% Al, 4-6% Mo, 3-5% V, 0.2-2.5% Zr, with the balance being Ti and unavoidable impurities; Methods for preparing high-strength and high-toughness powder metallurgy titanium alloys include: After sintering to obtain powder metallurgy titanium alloy billets, the billets are machined and chamfered, then placed in a resistance heating furnace for heat preservation, and forged according to a high-low-high forging process. The first forging temperature is 10~30 ℃ above the alloy phase transformation point; the second and third forging temperatures are 30~50 ℃ below the alloy phase transformation point; the fourth forging temperature is 10~30 ℃ below the alloy phase transformation point. After forging, the billets are air-cooled to obtain forged billets. The forging billet is subjected to a two-stage annealing heat treatment, with air cooling or cooling at a rate of 0.1~1 ℃ / min between the two stages of annealing; after the second stage of annealing, it is removed from the furnace and air cooled to obtain a high-strength and high-toughness powder metallurgy titanium alloy.
[0008] The high-strength and high-toughness powder metallurgy titanium alloy provided by the present invention may optionally be composed of the following components by mass percentage: 2-4% Al, 4-6% Mo, 3-5% V, 0.3-0.7% Zr, with the balance being Ti and unavoidable impurities. More specifically, the components may be proportioned as follows by mass percentage: Al 2.8-3.3%, Mo 4.8-5.3%, V 4.3-4.8%, Zr 0.4-0.6%, with the balance being Ti and unavoidable impurities.
[0009] The high-strength and high-toughness powder metallurgy titanium alloy provided by the present invention may optionally be composed of the following components by mass percentage: 2-4% Al, 4-6% Mo, 3-5% V, 0.8-1.2% Zr, with the balance being Ti and unavoidable impurities. More specifically, the components may be proportioned as follows by mass percentage: Al 2.8-3.3%, Mo 4.8-5.3%, V 4.3-4.8%, Zr 0.9-1.1%, with the balance being Ti and unavoidable impurities.
[0010] The high-strength and high-toughness powder metallurgy titanium alloy provided by the present invention may optionally be composed of the following components by mass percentage: 2-4% Al, 4-6% Mo, 3-5% V, 1.3-1.7% Zr, with the balance being Ti and unavoidable impurities. More specifically, the components may be proportioned as follows by mass percentage: Al 2.8-3.3%, Mo 4.8-5.3%, V 4.3-4.8%, Zr 1.4-1.6%, with the balance being Ti and unavoidable impurities.
[0011] The high-strength and high-toughness powder metallurgy titanium alloy provided by the present invention may optionally be composed of the following components by mass percentage: 2-4% Al, 4-6% Mo, 3-5% V, 1.8-2.2% Zr, with the balance being Ti and unavoidable impurities. More specifically, the components may be proportioned as follows by mass percentage: Al 2.8-3.3%, Mo 4.8-5.3%, V 4.3-4.8%, Zr 1.9-2.1%, with the balance being Ti and unavoidable impurities.
[0012] According to another aspect of the present invention, a method for preparing a high-strength and high-toughness powder metallurgy titanium alloy as described in any of the preceding claims is provided, comprising: S1. Prepare the titanium alloy powder according to the mass percentage and mix them evenly; S2. The uniformly mixed alloy powder is filled into a cold isostatic pressing sleeve, vacuum-sealed, pressurized to the set pressure and held to press into a cylindrical green billet. S3. Place the cylindrical green billet into a vacuum sintering furnace and sinter it under vacuum conditions to obtain a powder metallurgy titanium alloy sintered billet. S4. After machining and chamfering the billet, place it in a resistance heating furnace for heat preservation, and forge it according to the high-low-high forging process. The forging temperature of the first forging is 10~30 ℃ above the alloy phase transformation point; the forging temperatures of the second and third forgings are 30~50 ℃ below the alloy phase transformation point; the forging temperature of the fourth forging is 10~30 ℃ below the alloy phase transformation point. After forging, air cooling is performed to obtain the forged billet. S5. Perform a two-stage annealing heat treatment on the forging billet, with air cooling or cooling at a rate of 0.1~1 ℃ / min between the two stages of annealing; after the second stage of annealing, remove the billet from the furnace and air cool to obtain a high-strength and high-toughness powder metallurgy titanium alloy.
[0013] According to the preparation method provided by the present invention, optionally, the forging temperature of the first forging in S4 is 20°C above the alloy phase transformation point; the forging temperatures of the second and third forgings are 40°C below the alloy phase transformation point; the forging temperature of the fourth forging is 10°C below the alloy phase transformation point; each forging is carried out by a one-upsetting and one-drawing deformation method, and the deformation amount per forging is 30~60%; if the temperature drop exceeds 150°C during each forging process, it is reheated in the furnace.
[0014] According to the preparation method provided by the present invention, optionally, the chamfer radius in S4 is R5~30; the holding time in the resistance heating furnace for each forging is t=1 / 2D+(15~40), where t is in min and D is the billet diameter in mm.
[0015] According to the preparation method provided by the present invention, optionally, the first annealing temperature in S5 is 80~100 ℃ below the alloy phase transformation point; the second annealing temperature is 280~300 ℃ below the alloy phase transformation point.
[0016] According to the preparation method provided by the present invention, optionally, air cooling or furnace cooling at a cooling rate of 0.5 °C / min is used between the two annealing stages.
[0017] In summary, compared with the prior art, the high-strength and high-toughness powder metallurgy titanium alloy and its preparation method provided by this invention are superior: 1. The titanium alloy material system provided by the present invention avoids grain boundary embrittlement and improves crack propagation resistance through Mo-V binary β-stabilized composition design. By adding different concentrations of Zr, the distribution of Zr in the α / β phases is controlled, and the coordinated deformation ability of the two phases is adjusted. This achieves multiple effects such as improving impact toughness at the same strength level, improving strength at the same impact toughness level, or simultaneously improving yield strength and impact toughness. 2. The preparation, processing, and performance control methods of the titanium alloy are also provided: powder metallurgy preparation is carried out according to the component ratio, including powder mixing, pressing, and sintering. Forging is carried out sequentially at three initial forging temperatures: 10~30 ℃ above the alloy phase transformation point, 30~50 ℃ below the alloy phase transformation point, and 10~30 ℃ below the alloy phase transformation point. Two-stage annealing treatment is carried out sequentially at two temperatures, and the air cooling or cooling rate between the two stages is controlled to be 0.1~1 ℃ / min. Finally, a composite bimodal structure composed of equiaxed primary α, fine dispersed secondary α, and stable transformation β, as well as an equiaxed structure, is obtained, which effectively balances solid solution strengthening and slip-coordinated deformation. A comprehensive microstructure control system covering composition, densification, deformation, and heat treatment has been established, ensuring repeatable and achievable strengthening and toughening effects. This system is not only innovative in its composition design but also establishes a matching full-process technology system, forming a closed-loop control mechanism from alloy composition to final microstructure and properties. 3. This invention achieves a level of strength and toughness synergy that is difficult to reach with existing technologies: Based on the above-mentioned composition-structure-process synergistic design, this invention achieves multi-level control of strength and toughness from the lattice scale, phase transformation scale, interface scale to microstructure scale, which not only significantly improves the alloy strength but also greatly enhances the impact toughness, enabling the material to possess both high load-bearing capacity and excellent crack resistance. Especially in terms of impact toughness, this invention reaches 163.1 J / cm², far exceeding the level reported in existing patents, indicating that it has superior comprehensive performance in crack initiation inhibition, propagation blocking, and plastic energy dissipation; 4. The titanium alloy of this invention has a yield strength of 776.6~989.9 MPa, a tensile strength of 792.6~1030.2 MPa, an elongation after fracture of 14.7%~21.5%, and an impact toughness of 58.2~163.1 J / cm². This alloy is suitable for deep-earth drilling, shipborne equipment, and components subjected to high impact loads. Attached Figure Description
[0018] Figure 1 This is a SEM image of the high-strength and high-toughness titanium alloy prepared in Example 1.
[0019] Figure 2 This is a SEM image of the high-strength and high-toughness titanium alloy prepared in Example 5.
[0020] Figure 3 This is a comparison of the tensile properties and impact toughness of Examples 1-4 and Comparative Example 1.
[0021] Figure 4 This is a comparison of the tensile properties and impact toughness of Examples 5-8 and Comparative Example 2. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.
[0023] Please see Figure 1 and Figure 2 This application provides a high-strength and high-toughness powder metallurgy titanium alloy, which is composed of the following components by mass percentage: 2-4% Al, 4-6% Mo, 3-5% V, 0.2-2.5% Zr, with the balance being Ti and unavoidable impurities.
[0024] Based on the high-strength and high-toughness powder metallurgy titanium alloy composition system provided in the embodiments of this application, a comparative example is constructed. This comparative example provides a powder metallurgy titanium alloy composed of the following components by mass percentage: 2-4% Al, 4-6% Mo, 3-5% V, with the balance being Ti and unavoidable impurities. This comparative example leverages the high homogeneity of powder metallurgy, achieving a yield strength of 770-930 MPa and an impact toughness of 55-65 J / cm² through the aforementioned low-Al, high-Mo, and high-V alloying element ratio of 2-4% Al, 4-6% Mo, and 3-5% V. 2 Basic performance.
[0025] Based on the aforementioned fundamental properties, this application embodiment improves the impact toughness by 45-100 J / cm² at the same yield strength level by adding different amounts of the 0.2-2.5% neutral Zr element that tends to be enriched in the β phase. 2 Alternatively, the yield strength can be increased by 25-60 MPa at the same level of impact toughness, or the yield strength and impact toughness can be increased simultaneously.
[0026] In some alternative embodiments, the high-strength and high-toughness powder metallurgy titanium alloy is composed of the following components by mass percentage: 2-4% Al, 4-6% Mo, 3-5% V, 0.3-0.7% Zr, with the balance being Ti and unavoidable impurities. The addition of a small amount of Zr reduces the hardness difference between the α and β phases, improving the ability of the two phases to coordinate deformation. The titanium alloy exhibits a yield strength of 770-930 MPa and an impact toughness of 100-165 J / cm². 2 .
[0027] In some alternative embodiments, the high-strength and high-toughness powder metallurgy titanium alloy is composed of the following components by mass percentage: 2-4% Al, 4-6% Mo, 3-5% V, 0.8-1.2% Zr, with the balance being Ti and unavoidable impurities. The addition of a small amount of Zr reduces the hardness difference between the α and β phases, improving the ability of the two phases to coordinate deformation. The titanium alloy exhibits a yield strength of 780-930 MPa and an impact toughness of 85-110 J / cm². 2 .
[0028] In some alternative embodiments, the high-strength and high-toughness powder metallurgy titanium alloy is composed of the following components by mass percentage: 2-4% Al, 4-6% Mo, 3-5% V, 1.3-1.7% Zr, with the balance being Ti and unavoidable impurities. By increasing the Zr content relative to the composition system of the above embodiments, the solid solution strengthening effect of Zr in the α phase is enhanced; the titanium alloy has a yield strength of 800-950 MPa and an impact toughness of 65-85 J / cm. 2 .
[0029] In some alternative embodiments, the high-strength and high-toughness powder metallurgy titanium alloy is composed of the following components by mass percentage: 2-4% Al, 4-6% Mo, 3-5% V, 1.8-2.2% Zr, with the balance being Ti and unavoidable impurities. By further increasing the Zr content relative to the composition system of the above embodiments, the Zr content dissolved in the α phase is increased; the titanium alloy has a yield strength of 800-990 MPa and an impact toughness of 58.2-80 J / cm. 2 .
[0030] The Zr content ratio and performance control mechanism in the above embodiments differ from existing technologies. The core mechanism of adding Zr in existing technologies usually lies in achieving coupling strengthening of the α phase through Zr and Al elements, using Zr to replace part of the Al element, suppressing the precipitation of Ti3Al intermetallic compounds during long-term aging, and avoiding excessive solid solution of the α phase that would severely damage the plasticity and toughness of the titanium alloy.
[0031] This application utilizes the properties of Zr as a substitutional neutral element, which does not significantly alter the ratio of the two phases and tends to enrich the β phase while providing superior strengthening to the α phase. By adding Zr at different ratios, the deformation mechanism and coordinated deformation capacity of the two phases during load-bearing are precisely controlled, thereby achieving multiple effects such as improving impact toughness at the same strength level, improving strength at the same impact toughness level, or simultaneously improving yield strength and impact toughness. In the low Zr content range of <0.7%, Zr is mainly concentrated in the β phase, effectively reducing the hardness difference between the α and β phases and improving the coordinated deformation capacity of the two phases. This significantly improves the impact toughness at the same strength level, with a maximum impact toughness of 163.1 J / cm², which is not only significantly better than the 35~45.8 J / cm² reported in other related technologies, but also reaches the highest level reported to date.
[0032] When the Zr content increases to 0.8–1.2%, the material remains in the stress-induced martensitic deformation region. At this point, the redistribution of Zr between the α and β phases disrupts the original hardness matching. This exacerbated two-phase plasticity mismatch not only weakens the material's synergistic deformation capability, reducing impact toughness to 107.2 J / cm², but also restricts the overall solid solution strengthening effect of Zr on the matrix, causing its gain to plateau, resulting in the overall macroscopic strength of the material remaining essentially unchanged. However, as the Zr content further increases to the high Zr content range of 1.3–2.5%, the material system gradually approaches the "martensite-twin" deformation region. At this point, more Zr is dissolved in the α phase, effectively improving the strength level not only due to its higher solid solution strengthening effect on the α phase (compared to the β phase), but also by altering the stacking fault energy, adjusting the deformation mechanism under impact to be dominated by deformation twins, thus maintaining relatively excellent impact toughness. This is a key innovation of this application's embodiments that distinguishes it from existing technologies.
[0033] The material system provided in this application also constructs a Mo-V binary β-stabilized system to avoid grain boundary embrittlement caused by fast eutectoid elements and improve crack propagation resistance. Unlike existing technologies that often use fast eutectoid β-stabilizing elements such as Cr and Fe, this application abandons element systems that easily induce segregation and grain boundary embrittlement, and adopts a Mo-V binary β-stabilized design. Mo, as a slow-diffusion β-stabilizing element, can significantly improve the thermal stability of the β phase, widen the processing window of the two-phase region, and provide sufficient process margin for controllable microstructure evolution; V, relying on its high solid solution capacity in the β phase and interfacial segregation effect, reduces the α / β interfacial energy and suppresses the precipitation of continuous network α phase at grain boundaries.
[0034] More importantly, the synergistic effect of Mo and V can jointly regulate the β→α phase transformation kinetics, causing the secondary α phase to precipitate in a fine, discrete, and diffuse distribution, rather than forming continuous lamellar or network channels along grain boundaries. This microstructure significantly weakens the continuous path of rapid crack propagation along grain boundaries, improving crack deflection, bifurcation, and passivation capabilities, thereby enhancing toughness at the phase transformation and interface level. Compared to existing technologies that mainly rely on passive toughening after strength enhancement, the embodiments of this application achieve the effect of actively constructing crack-resistant microstructure units through β phase stability design.
[0035] In addition, Zr has a more prominent neutral solid solution and synergistic stabilizing effect in dual-phase matrices, which can simultaneously optimize strength, plasticity and microstructure stability.
[0036] This application fully utilizes the high solid solution properties of Zr as a substitutional neutral element in both the α and β phases. Unlike the unidirectional driving effect of purely α- or β-stable elements on phase equilibrium, it achieves more compatible and uniform strengthening within a two-phase matrix. Zr not only provides a stable solid solution strengthening effect but also effectively lowers the martensite initiation temperature, improves the retention of the metastable β phase during cooling, suppresses diffusionless brittle phase transformation, and reduces the tendency for brittle structures such as α′ martensite to form.
[0037] Furthermore, Zr exhibits a significant synergistic regulatory effect with Mo and V, which can further influence the stability of the β matrix and element diffusion behavior, promote the uniform precipitation of fine, dispersed α phases, and inhibit the formation of brittle transition phases such as the ω phase. By controlling the Zr content within a reasonable range, the embodiments of this application effectively optimize the precipitation path and microstructure stability without disrupting the original two-phase equilibrium, reducing the embrittlement sensitivity during heat treatment and cooling, thereby significantly broadening the plasticity-toughness matching window of the high-strength titanium alloy. This mechanism determines that the embodiments of this application are not simply "strengthening with Zr," but rather achieve a design that combines two-phase microstructure stabilization with strength-toughness synergy under the participation of neutral elements.
[0038] Furthermore, embodiments of this application also provide a method for preparing a high-strength and high-toughness powder metallurgy titanium alloy as described in any of the above claims, the method comprising: S1. Prepare the titanium alloy powder according to the mass percentage and mix them evenly; S2. The uniformly mixed alloy powder is filled into a cold isostatic pressing sleeve, vacuum-sealed, pressurized to the set pressure and held to press into a cylindrical green billet. S3. Place the cylindrical green billet into a vacuum sintering furnace and sinter it under vacuum conditions to obtain a powder metallurgy titanium alloy sintered billet. S4. After machining and chamfering the billet, place it in a resistance heating furnace for heat preservation, and forge it according to the high-low-high forging process. The forging temperature of the first forging is 10~30 ℃ above the alloy phase transformation point; the forging temperatures of the second and third forgings are 30~50 ℃ below the alloy phase transformation point; the forging temperature of the fourth forging is 10~30 ℃ below the alloy phase transformation point. After forging, air cooling is performed to obtain the forged billet. S5. The forging billet undergoes a two-stage annealing heat treatment, with air cooling or cooling at a rate of 0.1~1 ℃ / min between the two stages of annealing; after the second stage of annealing, it is removed from the furnace and air-cooled to obtain a high-strength and high-toughness titanium alloy. More preferably, air cooling or furnace cooling at a rate of 0.5 ℃ / min is used between the two stages of annealing.
[0039] This application establishes a comprehensive microstructure control system covering composition, densification, deformation, and heat treatment, ensuring repeatable and achievable strengthening and toughening effects. This application not only features innovative composition design but also establishes a matching full-process system, forming a closed-loop control mechanism from alloy composition to final microstructure and properties.
[0040] In the densification stage of powder metallurgy, a composite technology of cold isostatic pressing-sintering-forging is used to achieve near-net-shape forming and high-density preparation. The process is accompanied by full element diffusion, pore closure and microstructure refinement, which lays a good foundation for subsequent dual-state microstructure control.
[0041] In the two-phase region forging stage with fewer passes, this embodiment adopts a high-low-high forging temperature path. By precisely controlling the forging temperature of each pass, the advantages of deformation and microstructure control in different phase regions are fully utilized. Specifically, the first forging temperature is set 10–30 °C above the alloy's phase transformation point to improve the alloy's plastic deformation capacity, promote the closure of residual pores, and fully break down the original microstructure. Simultaneously, strictly controlling the forging temperature within a narrow temperature range above the phase transformation point effectively suppresses abnormal coarsening of β grains caused by excessively high temperatures in conventional β-region forging. The second and third forging temperatures are lowered to 30–50 °C below the phase transformation point. At this point, the matrix deformation resistance increases, and by applying a single large deformation plastic process, a high amount of deformation energy is accumulated within the material, thereby promoting dynamic recrystallization and full breakage of the lamellar α phase, further refining the microstructure. The fourth forging temperature is increased to 10–30 °C below the phase transformation point, promoting material forming while further stabilizing the post-forging deformed microstructure. The aforementioned gradient temperature control path, combined with a forging process involving fewer heating cycles and greater deformation, effectively avoids the problems of β-grain coarsening and microstructure dispersion caused by repeated heating cycles in traditional methods, while achieving sufficient microstructure refinement and homogenization.
[0042] In the two-stage annealing and controlled cooling stages, the annealing temperature and cooling rate are precisely controlled to achieve phased regulation of the spheroidization of the primary α phase, the precipitation of the secondary α phase, and the stabilization of the phase boundaries. The first-stage annealing temperature is set at 80–100 °C below the alloy's phase transformation point. This temperature range can effectively eliminate forging residual stress and is conducive to the spheroidization and equiaxing of the fragmented lamellar α phase in the early stage, thereby improving the impact toughness of the alloy. The second-stage annealing temperature is lowered to 280–300 °C below the alloy's phase transformation point. By further eliminating residual stress and stabilizing the microstructure, the microstructure is further regulated. When air cooling is used between the two annealing stages, the faster cooling rate promotes the dispersed precipitation of fine secondary α phases in the β phase and inhibits their excessive growth, refining the α / β microstructure and stabilizing the two-phase interface. This results in a composite dual-state microstructure of "equiaxed primary α + fine dispersed secondary α + stable transformation β," achieving a balance between high strength and good impact toughness. When controlled slow cooling at 0.1~1℃ / min is used, element redistribution and further spheroidization and growth of the α phase are promoted, forming an equiaxed microstructure with high strength and extremely high impact toughness. Through the synergistic control of the specific temperature path and cooling method described above, the embodiments of this application can achieve the preparation of microstructures with different strength and toughness properties, effectively transforming the advantages of compositional design into stable strength and toughness performance advantages, demonstrating good process feasibility and industrial scale-up potential.
[0043] The following are specific examples, Example 1: This embodiment provides a method for preparing a high-strength and high-toughness powder metallurgy titanium alloy, comprising the following steps: S1. Alloy powder preparation and mixing: The powder is prepared by mass percentage as follows: Al 3.0%, Mo 5.0%, V 4.5%, Zr 0.5%, with the balance being Ti and unavoidable impurities; a conical mixer with argon protection is used to mix at a speed of 50 r / min for 10 hours to ensure uniform mixing.
[0044] S2. Cold isostatic pressing: The alloy powder from step S1 is loaded into a sleeve and placed in a cold isostatic pressing device, and pressed with a pressing force of 250 MPa for 20 min to obtain a powder metallurgy titanium alloy green billet.
[0045] S3. Vacuum sintering: Place the green blank obtained in step S2 into a vacuum sintering furnace and evacuate it to a vacuum level of 1×10⁻⁶. -4 After Pa, the temperature is increased. During the heating process, there are 6 holding sections, each holding for 30 minutes. The temperature is finally increased to 1300 ℃ and held for 3 hours. After cooling, sintered ingots are obtained.
[0046] S4. Forging and forming: The phase transformation point T of the alloy is determined using metallographic methods. βThe sintered ingot obtained in step S3 is chamfered at both ends with a chamfer radius of R8. It is then forged after holding at each forging temperature. The first forging temperature (i.e., the initial forging temperature) is 20°C above the alloy phase transformation point; the second and third forging temperatures are both 40°C below the alloy phase transformation point; and the fourth forging temperature (i.e., the drawing temperature) is 10°C below the alloy phase transformation point. Each forging cycle uses a one-up-one-drawing deformation method, with a forging deformation of 55% per cycle. The temperature drop during forging must not exceed 150°C. If the temperature drop exceeds 150°C during any forging cycle, the ingot is returned to the furnace, held at the same temperature again, and forged again. After forging, it is air-cooled to obtain the forged billet.
[0047] The holding time for each forging in the resistance heating furnace is t = 1 / 2D + 30, where t is in minutes and D is the billet diameter in mm.
[0048] S5. Heat Treatment: The forged billet obtained in step S4 is subjected to heat treatment to obtain a high-strength and high-toughness titanium alloy. The heat treatment process is a two-stage annealing. The first stage annealing temperature is 80~100 ℃ below the alloy phase transformation point; the second stage annealing temperature is 280~300 ℃ below the alloy phase transformation point. More specifically, the first stage annealing temperature is 80 ℃ below the alloy phase transformation point, held at this temperature for 2 hours, and then air-cooled; the second stage annealing temperature is 280 ℃ below the alloy phase transformation point, held at this temperature for 2 hours, and then air-cooled to obtain the high-strength and high-toughness titanium alloy.
[0049] The high-strength and high-toughness titanium alloy prepared in this embodiment has a yield strength of 927.5 MPa, a tensile strength of 982.4 MPa, an elongation at break of 17.5%, and an impact toughness of 103.8 J / cm². 2 .
[0050] Example 2: To prepare a high-strength and high-toughness titanium alloy, the following ingredients were prepared by mass percentage: Al 3.0%, Mo 5.0%, V 4.5%, Zr 1.0%, with the balance being Ti and unavoidable impurities. Other process steps were the same as in Example 1.
[0051] The high-strength and high-toughness titanium alloy prepared in this embodiment has a yield strength of 926.8 MPa, a tensile strength of 982.8 MPa, an elongation at break of 17.6%, and an impact toughness of 88.4 J / cm. 2 .
[0052] Example 3: To prepare a high-strength and high-toughness titanium alloy, the following ingredients were prepared by mass percentage: Al 3.0%, Mo 5.0%, V 4.5%, Zr 1.5%, with the balance being Ti and unavoidable impurities. Other process steps were the same as in Example 1.
[0053] The high-strength and high-toughness titanium alloy prepared in this embodiment has a yield strength of 945.7 MPa, a tensile strength of 998.6 MPa, an elongation at break of 17.7%, and an impact toughness of 68.5 J / cm. 2 .
[0054] Example 4: To prepare a high-strength and high-toughness titanium alloy, the following ingredients were prepared by mass percentage: Al 3.0%, Mo 5.0%, V 4.5%, Zr 2.0%, with the balance being Ti and unavoidable impurities; other process steps were the same as in Example 1.
[0055] The high-strength and high-toughness titanium alloy prepared in this embodiment has a yield strength of 989.9 MPa, a tensile strength of 1030.2 MPa, an elongation at break of 14.7%, and an impact toughness of 58.2 J / cm². 2 .
[0056] Example 5: A high-strength and high-toughness titanium alloy is prepared by the following method: S1. Alloy Powder Preparation and Mixing: The powder is prepared by mass percentage as follows: Al 3.0%, Mo 5.0%, V 4.5%, Zr 0.5%, with the balance being Ti and unavoidable impurities. An argon-protected conical mixer is used, and the mixture is stirred at 50 r / min for 10 hours to ensure uniform mixing.
[0057] S2. Cold isostatic pressing: The alloy powder from step S1 is loaded into a sleeve and placed in a cold isostatic pressing device, and pressed with a pressing force of 250 MPa for 20 min to obtain a titanium alloy green billet.
[0058] S3. Vacuum sintering: Place the green blank obtained in step S2 into a vacuum sintering furnace and evacuate it to a vacuum level of 1×10⁻⁶. -4 After Pa, the temperature is increased. During the heating process, there are 6 holding sections, each holding for 30 minutes. The temperature is finally increased to 1300℃ and held for 3 hours. After cooling, sintered ingots are obtained.
[0059] S4. Forging and forming: The phase transformation point T of the alloy is determined using metallographic methods. β The sintered ingot obtained in step S3 is rounded at both ends with R8 radius, held at a certain temperature, and then forged. The forging temperature for the first firing is 20°C above the alloy phase transformation point; the forging temperatures for the second and third firings are both 40°C below the alloy phase transformation point; the drawing temperature for the fourth firing is 10°C below the alloy phase transformation point, and the deformation amount for each firing is 55%. The temperature drop during forging must not exceed 150°C, and the forged billet is obtained by air cooling after forging.
[0060] S5. Heat Treatment: The forged billet obtained in step S4 is heat-treated to obtain a high-strength and high-toughness titanium alloy. The heat treatment process is a two-stage annealing. The first stage annealing temperature is 80 ℃ below the alloy phase transformation point. After holding at this temperature for 2 hours, it is cooled at a rate of 0.5 ℃ / min to the second stage annealing temperature (280 ℃ below the alloy phase transformation point). After holding at this temperature for 2 hours, it is air-cooled. This controlled cooling method helps the spheroidization of the primary α phase and the formation of an equiaxed structure, providing conditions for a significant improvement in toughness.
[0061] The high-strength and high-toughness titanium alloy prepared in this embodiment has a yield strength of 776.6 MPa, a tensile strength of 792.6 MPa, an elongation at break of 21.5%, and an impact toughness of 163.1 J / cm². 2 .
[0062] Example 6: To prepare a high-strength and high-toughness titanium alloy, the following ingredients were prepared by mass percentage: Al 3.0%, Mo 5.0%, V 4.5%, Zr 1.0%, with the balance being Ti and unavoidable impurities. The other process steps were the same as in Example 5.
[0063] The high-strength and high-toughness titanium alloy prepared in this embodiment has a yield strength of 780.1 MPa, a tensile strength of 797.7 MPa, an elongation at break of 22.2%, and an impact toughness of 107.2 J / cm². 2 .
[0064] Example 7: To prepare a high-strength and high-toughness titanium alloy, the following ingredients were prepared by mass percentage: Al 3.0%, Mo 5.0%, V 4.5%, Zr 1.5%, with the balance being Ti and unavoidable impurities. Other process steps were the same as in Example 5.
[0065] The high-strength and high-toughness titanium alloy prepared in this embodiment has a yield strength of 803.3 MPa, a tensile strength of 811.2 MPa, an elongation at break of 20.7%, and an impact toughness of 83.1 J / cm. 2 .
[0066] Example 8: To prepare a high-strength and high-toughness titanium alloy, the following ingredients were prepared by mass percentage: Al 3.0%, Mo 5.0%, V 4.5%, Zr 2.0%, with the balance being Ti and unavoidable impurities. Other process steps were the same as in Example 5.
[0067] The high-strength and high-toughness titanium alloy prepared in this embodiment has a yield strength of 809.5 MPa, a tensile strength of 823.0 MPa, an elongation at break of 18.7%, and an impact toughness of 77.1 J / cm. 2 .
[0068] Comparative Example 1: The prepared powder metallurgical titanium alloy was prepared with the following mass percentages: Al 3.0%, Mo 5.0%, V 4.5%, with the balance being Ti and unavoidable impurities. Other steps were the same as in Example 1.
[0069] The powder metallurgical titanium alloy prepared in this comparative example has a yield strength of 930.1 MPa, a tensile strength of 995.4 MPa, an elongation at break of 15.6%, and an impact toughness of 55.4 J / cm². 2 .
[0070] Comparative Example 2: The prepared powder metallurgical titanium alloy was prepared with the following mass percentages: Al 3.0%, Mo 5.0%, V 4.5%, with the balance being Ti and unavoidable impurities. Other steps were the same as in Example 5.
[0071] The powder metallurgical titanium alloy prepared in this comparative example has a yield strength of 778.2 MPa, a tensile strength of 795.5 MPa, an elongation at break of 19.3%, and an impact toughness of 64.7 J / cm². 2 .
[0072] The mechanical property test results of the powder metallurgy titanium alloys prepared in Examples 1-8 and Comparative Examples 1-2 are summarized in Table 1.
[0073] Table 1 Summary of Mechanical Performance Test Results
[0074] In summary, for reference Figure 3 and Figure 4 This invention, through an integrated design of "composition-process-structure-performance," introduces Zr element and precisely controls its proportion to optimize the microstructure evolution during forging and heat treatment. Combined with powder metallurgy densification, "high-low-high" low-heat forging, and a "two-stage annealing + controlled cooling" heat treatment process, it effectively suppresses the initiation of brittle ω phase and microcracks. Thus, while maintaining a high strength level of ≥770 MPa, it increases the impact toughness to 163.1 J / cm², breaking through the bottleneck of balancing strength, plasticity, and toughness in powder metallurgy titanium alloys. The powder metallurgy titanium alloy proposed in this invention has broad application prospects in deep earth drilling, the petroleum industry, and high-impact service equipment.
[0075] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A high-strength and high-toughness powder metallurgy titanium alloy, characterized in that, It consists of the following components by mass percentage: 2-4% Al, 4-6% Mo, 3-5% V, 0.2-2.5% Zr, with the balance being Ti and unavoidable impurities; Methods for preparing high-strength and high-toughness powder metallurgy titanium alloys include: After sintering to obtain powder metallurgy titanium alloy billets, the billets are machined and chamfered, then placed in a resistance heating furnace for holding at a certain temperature, and forged according to a high-low-high forging process. The first forging temperature is 10~30 ℃ above the alloy phase transformation point; the second and third forging temperatures are 30~50 ℃ below the alloy phase transformation point; the fourth forging temperature is 10~30 ℃ below the alloy phase transformation point. After forging, the billets are air-cooled to obtain forged billets. The forging billet is subjected to a two-stage annealing heat treatment, with air cooling or cooling at a rate of 0.1~1 ℃ / min between the two stages of annealing; after the second stage of annealing, it is removed from the furnace and air cooled to obtain a high-strength and high-toughness powder metallurgy titanium alloy.
2. The high-strength and high-toughness powder metallurgy titanium alloy as described in claim 1, characterized in that, It consists of the following components by mass percentage: 2-4% Al, 4-6% Mo, 3-5% V, 0.3-0.7% Zr, with the balance being Ti and unavoidable impurities.
3. The high-strength and high-toughness powder metallurgy titanium alloy as described in claim 1, characterized in that, It consists of the following components by mass percentage: 2-4% Al, 4-6% Mo, 3-5% V, 0.8-1.2% Zr, with the balance being Ti and unavoidable impurities.
4. The high-strength and high-toughness powder metallurgy titanium alloy as described in claim 1, characterized in that, It consists of the following components by mass percentage: 2-4% Al, 4-6% Mo, 3-5% V, 1.3-1.7% Zr, with the balance being Ti and unavoidable impurities.
5. The high-strength and high-toughness powder metallurgy titanium alloy as described in claim 1, characterized in that, It consists of the following components by mass percentage: 2-4% Al, 4-6% Mo, 3-5% V, 1.8-2.2% Zr, with the balance being Ti and unavoidable impurities.
6. A method for preparing a high-strength and high-toughness powder metallurgy titanium alloy as described in any one of claims 1-5, characterized in that, include: S1. Prepare the titanium alloy powder according to the mass percentage and mix them evenly; S2. The uniformly mixed alloy powder is filled into a cold isostatic pressing sleeve, vacuum-sealed, pressurized to the set pressure and held to press into a cylindrical green billet. S3. Place the cylindrical green billet into a vacuum sintering furnace and sinter it under vacuum conditions to obtain a powder metallurgy titanium alloy sintered billet. S4. After machining and chamfering the billet, place it in a resistance heating furnace for heat preservation, and forge it according to the high-low-high forging process. The forging temperature of the first forging is 10~30 ℃ above the alloy phase transformation point; the forging temperatures of the second and third forgings are 30~50 ℃ below the alloy phase transformation point; the forging temperature of the fourth forging is 10~30 ℃ below the alloy phase transformation point. After forging, air cooling is performed to obtain the forged billet. S5. Perform a two-stage annealing heat treatment on the forging billet, with air cooling or cooling at a rate of 0.1~1 ℃ / min between the two stages of annealing; after the second stage of annealing, remove the billet from the furnace and air cool to obtain a high-strength and high-toughness powder metallurgy titanium alloy.
7. The preparation method according to claim 6, characterized in that, In S4, the first forging temperature is 20°C above the alloy phase transformation point; the second and third forging temperatures are 40°C below the alloy phase transformation point; and the fourth forging temperature is 10°C below the alloy phase transformation point. Each forging process uses a one-upsetting and one-drawing deformation method, with a deformation amount of 30-60% per forging. If the temperature drop exceeds 150°C during each forging process, the furnace is reheated for heat preservation.
8. The preparation method according to claim 6, characterized in that, The chamfer radius in S4 is R5~30; the holding time for each forging in the resistance heating furnace is t=1 / 2D+(15~40), where t is in min and D is the billet diameter in mm.
9. The preparation method according to claim 6, characterized in that, In S5, the first annealing temperature is 80~100 ℃ below the alloy phase transformation point; the second annealing temperature is 280~300 ℃ below the alloy phase transformation point.
10. The preparation method according to claim 6, characterized in that, Between the two annealing stages, air cooling or furnace cooling at a rate of 0.5 ℃ / min is used.
Citation Information
Patent Citations
A high-toughness titanium alloy with a yield strength higher than 900 MPa and its preparation method
CN110229976B
827MPa-grade high-strength high-toughness titanium alloy drill rod pipe for deep well and large-strain short-process preparation method and application thereof
CN120026211A